Anisotropic flow in Xe-Xe collisions at √sNN=5.44 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Klewin, Sebastian; Leardini, Lucia; et al. (Physics letters, 2018)
The first measurements of anisotropic flow coefficients vn for mid-rapidity charged particles in Xe-Xe collisions at sNN=5.44 TeV are presented. Comparing these measurements to those from Pb-Pb collisions at sNN=5.02 TeV, v2 is found to be suppressed for mid-central collisions at the same centrality, and enhanced for central collisions. The values of v3 are generally larger in Xe-Xe than in Pb-Pb at a given centrality. These observations are consistent with expectations from hydrodynamic predictions. When both v2 and v3 are divided by their corresponding eccentricities for a variety of initial state models, they generally scale with transverse density when comparing Xe-Xe and Pb-Pb, with some deviations observed in central Xe-Xe and Pb-Pb collisions. These results assist in placing strong constraints on both the initial state geometry and medium response for relativistic heavy-ion collisions.
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, M.C. Danisch, A. Deisting, V. Feuillard, P. Glässel, J. Kim, M. Kim, M.K. Köhler, S. Klewin, L. Leardini, J. Mercado Pérez, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, M.O. Schmidt, J. Stachel, D.F. Weiser, B. Windelband [und weitere]
Gesehen am 18.06.2019